Tunable Crystalline Phases in UV-Curable PEG-Grafted Ladder-Structured Silsesquioxane/Polyimide Composites - Kim, Ryung Il; Shin, Ju Ho; Lee, Jong Suk; Lee, Jung-Hyun; Lee, Albert S.; Hwang, Seung Sang (MDPI Open Access Publishing, 2020)
A series of UV-curable hybrid composite blends containing a carboxylic acid functionalized polyimidewith varying amounts of high molecular weight (similar to 1 K) PEG-grafted ladder-structured polysilsesquioxanes copolymerized with methacryl groups were fabricated and their structural, thermal, mechanical, and surface properties characterized. At a composite weight ratio of polyimide above 50 wt.%, a stark shift from amorphous to crystalline polyethylene glycol (PEG) phases were observed, accompanied by a drastic increase in both surface moduli and brittleness index. Moreover, fabricated composites were shown to have a wide range water contact angle, 9.8 degrees-73.8 degrees, attesting to the tunable surface properties of these amphiphilic hybrid polymer composites. The enhanced mechanical properties, combined with the utility of tunable surface hydrophilicity allows for the possible use of these hybrid polymer composites to be utilized as photosensitive polyimide negative photoresists for a myriad of semiconductor patterning processes.